Frecuencia de infección por Trypanosoma sp. en búfalos de agua (Bubalus bubalis) en cuatro hatos bufaleros de Barrancabermeja, Colombia - Zapata, Richard; Mesa, Julián; Mejía, Jaime; Reyes, Julián; Ríos, Leonardo A. (Revista Colombiana de Ciencias Pecuarias, 2009)
Summary In Colombia the buffalo industry is developed mainly in tropical and subtropical areas, becoming an important economic resource, that can be affected by haemoparasite caused diseases, being Trypanosoma sp. one of the causal agents of great economic losses. We design a cross-sectional descriptive study with the objective to determine the frequency of Trypanosoma sp. in water buffaloes through direct parasitological tests in four ranches of Barrancabermeja (Middle Magdalena). Four ranches with a population of 1800 buffaloes were selected, where 209 samples were analyzed evaluating it by thin and thick smears stained with the Giemsa and Field techniques respectively. A medical-veterinary examination and a survey were done to each buffalo where the clinical and epidemiological data of each animal was briefed. By means of statistical analysis Ji-square and models of logistic regression significant statistical association between positivity to Trypanosoma sp. and buffaloes age was found, without symptoms and signs of disease. A value of 0.784 of agreement level was obtained between the thin and thick blood smears tests with Cohen’s Kappa index, that it means a substantial reproducibility between both tests to Trypanosoma sp. diagnosis in buffaloes.